A fish herpesvirus highlights functional diversities among Zα domains related to phase separation induction and A-to-Z conversion. Issue 2 (22nd September 2022) - Diallo, Mamadou Amadou; Pirotte, Sébastien; Hu, Yunlong; Morvan, Léa; Rakus, Krzysztof; Suárez, Nicolás M; PoTsang, Lee; Saneyoshi, Hisao; Xu, Yan; Davison, Andrew J; Tompa, Peter; Sussman, Joel L; et al.
Abstract: Zalpha (Zα) domains bind to left-handed Z-DNA and Z-RNA. The Zα domain protein family includes cellular (ADAR1, ZBP1 and PKZ) and viral (vaccinia virus E3 and cyprinid herpesvirus 3 (CyHV-3) ORF112) proteins. We studied CyHV-3 ORF112, which contains an intrinsically disordered region and a Zα domain. Genome editing of CyHV-3 indicated that the expression of only the Zα domain of ORF112 was sufficient for normal viral replication in cell culture and virulence in carp. In contrast, its deletion was lethal for the virus. These observations revealed the potential of the CyHV-3 model as a unique platform to compare the exchangeability of Zα domains expressed alone in living cells. Attempts to rescue the ORF112 deletion by a broad spectrum of cellular, viral, and artificial Zα domains showed that only those expressing Z-binding activity, the capacity to induce liquid-liquid phase separation (LLPS), and A-to-Z conversion, could rescue viral replication. For the first time, this study reports the ability of some Zα domains to induce LLPS and supports the biological relevance of dsRNA A-to-Z conversion mediated by Zα domains. This study expands the functional diversity of Zα domains and stimulates new hypotheses concerning the mechanisms of action of proteins containing Zα domains. Graphical Abstract: